Investigation of beam extraction and formation in the ions injector - Belikov, А.G.; Bondarenko, L.А.; Gussev, Ye.V.; Manuilenko, O.V.; Vdovin, S.А. (Вопросы атомной науки и техники, 2018)
The results of analytical and numerical studies an ion beam extraction and formation from a plasma source are presented. The influence of ion optics parameters on the ion beam characteristics is studied. The studies were carried out using a package of three-dimensional computer simulation of ion beams optics with allowance for space charge - IBSimu. The results show that of extraction electrode shape has an important role in shaping of the ion beam characteristics.